2011
DOI: 10.1002/tox.20782
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant effect of propolis against exposure to chromium inCyprinus carpio

Abstract: The aim of the present study was to investigate the ameliorative properties of propolis against the toxic effects of chromium (VI) by examining oxidative damage markers such as lipid peroxidation and the antioxidant defence system components in carp (Cyprinus carpio). The fish were exposed to sublethal concentrations of chromium. Propolis was simultaneously administered to chromium-exposed fish. Treatment was continued for 28 days, and at the end of this period, blood and tissue (liver, kidney, spleen, and gil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 65 publications
(83 reference statements)
2
23
0
Order By: Relevance
“…On the other hand, Tilapia fed the diet containing propolis nanoparticles and propolis combined with M. aeruginosa cells supplementation showed significant increment in the studied antioxidant activity levels and decrement in MDA level, respectively compared to (group 4) fish fed on diet mixed with M. aeruginosa cells only. These results are in cope with, (Yonar et al, 2014) who reported that simultaneous treatment with propolis decreased the severity of the oxidative stress induced by chromium in different tissues of common carp. (Zegura et al, 2011).…”
Section: Resultssupporting
confidence: 84%
“…On the other hand, Tilapia fed the diet containing propolis nanoparticles and propolis combined with M. aeruginosa cells supplementation showed significant increment in the studied antioxidant activity levels and decrement in MDA level, respectively compared to (group 4) fish fed on diet mixed with M. aeruginosa cells only. These results are in cope with, (Yonar et al, 2014) who reported that simultaneous treatment with propolis decreased the severity of the oxidative stress induced by chromium in different tissues of common carp. (Zegura et al, 2011).…”
Section: Resultssupporting
confidence: 84%
“…We also found that the exposure of rats to Na (2) Cr(2)O(7) for 8 consecutive days provoked renal damages with a significant increase in kidney MDA. Accordingly, Yonar et al reported that the levels of MDA, as an index of lipid peroxidation, increased as well as reduced GSH levels in Cyprinus carpio kidney treated with chromium (19). …”
Section: Discussionmentioning
confidence: 99%
“…Also, Yonar et al (2014) considered CPF exposure to as a stressor substance. In addition, Mazzon et al (2002) found that stress disrupts intestinal homeostasis and increase the intestinal permeability in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Attia et al (2012) stated that CPF treatment for 70 days cause significant reduction in antioxidant enzyme activities and elevation in lipid peroxidation level. In addition, Yonar et al (2014) stated that Lipid peroxidation is the initial step of cellular membrane damage.…”
Section: Discussionmentioning
confidence: 99%